Upaya Peningkatan Kesadaran Lingkungan Warga Desa Kayen melalui Revitalisasi Taman Desa - Anggi Indah Yuliana; Ana Mariatul Khiftiyah; Thohirin Thohirin; Ardy Ansyah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2021)
This community service activity aimed to increased community participation, especially youth, in maintaining cleanliness and environmental health through the revitalization of village parks. This activity was carried out at the Village Hall Park Kayen BandarKedungmulyo, Jombang with a total of about 20 members of the village youth organization in October 2020. The approach method for the implementation of this service activity included methods of socialization, discussion, and practiced. In the socialization activity, participants were given a brief module on environmental hygiene reflecting faith. Evaluation of results of village clean-up activities and revitalization of village parks. showed that the participants were quite enthusiastic and feel the benefits of this activity. It is hoped that the community, especially members of the youth organization, will be more creative in managing the village park to become a place for environmental creation so that it will attract the young generation of Kayen Village to develop parks in other village areas, not only in the village office area.